INOVASI STRATEGI PEMASARAN BANK SYARIAH DALAM MEMANFAATKAN TEKNOLOGI DIGITAL UNTUK MENINGKATKAN AKSES DAN KETERLIBATAN NASABAH - Wulan Ramadani Trisnaudy; Muhammad Iqbal Fasa; Is Susanto (Jurnal Intelek Dan Cendikiawan Nusantara, 2024)
This research explores the innovative marketing strategies implemented by Islamic banksin utilizing digital technology to increase customer access and engagement. In a digitalera characterized by high usage of mobile devices and social media, Islamic banks needto adapt to remain competitive. Through a qualitative approach with a literature studymethod, this research analyzes various relevant sources, including journal articles,industry reports, and policy documents, to identify best practices in the implementationof digital marketing strategies. The results show that the use of mobile applications andsocial media platforms effectively increase customer awareness of Islamic products andfacilitate better interaction between banks and customers. In addition, relevanteducational content, which emphasizes sharia values, is able to attract and buildcustomer loyalty. This study recommends that Islamic banks continue to innovate theirdigital marketing strategies to expand service access and enhance customer engagementin the digital era.